Orthodontic Removable Appliances - Shyam Lohkare Sandhya; Jaypee eBooks (Jaypee Brothers Medical Publisher (P) Ltd., 2008)
A complete and updated text explained in simplified and easy to grasp manner. This book focuses on important orthodontic removable appliances. This book includes all retentive parts, active parts, technique of wire bending, biomechanical considerations, modification for different malalignments. Removable appliances are the major culprit for preventive, and interceptive and corrective orthodontics. These appliances are simple to manage, economic and time saver, i.e. there is less time involvement of an orthodontist. This book is useful for students, teachers and practitioners of dentistry.
Keywords: Orthodontics and Dentofacial Orthopedics; Electronic books